ORGANOLEPTIC AND PROXIMATE CHARACTERISTICS OF COOKIES WITH TARO FLOUR (Colocasia Esculenta) SUBSTITUTION AS AN ALTERNATIVE SNACK - Dila Ayu Panandri; Junendri Ardian; Ni Made Wiasty Sukanty; M. Thonthowi Jauhari; Laksmi Nur Fajriani (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
Prediabetes is a condition charaterized by elevated blood glucose levels that have not yet reached the diagnostic threshold for diabetes mellitus. The rising prevalence of prediabetes has driven the development of low glycemic index snacks using local ingredients such as taro (Colocasia esculenta) and almonds (Prunus dulcis), which are rich in fiber and protein. This study aimed to evaluate the effect of incorporating taro root flour and almonds on the organoleptic properties and proximate composition of cookies intended as a healthy snack for individuals with prediabetes. A Completely Randomized Design (CRD) was applied. Organoleptic evaluation involved 40 semi-trained panelists, while proximate analysis was conducted in triplicate. The optimal formulation consisted of 25 g wheat flour and 75 g taro flour, producing cookies with a moderately distinctive taro flavor, acceptabel taste, and a fairly crispy texture. Although the sensory attributes were significantly affected (p<0.05), proximate analysis indicated significant differences (p<0.05) in moisture, ash, protein, fat, and carbohydrate content. These findings suggest that taro flour and almonds can enhance the nutritional quality of cookies and have potential as functional food products.